A popular history of France - from the earliest times (1870) (14594625067) - Internet Archive Book... (Wikimedia Commons, 1870)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons